Direct Dehydrative Glycosylation of C1‐Alcohols. Issue 20 (1st October 2018) - O'Neill, Sloane; Rodriguez, Jacob; Walczak, Maciej A.
Abstract: Due to the central role played by carbohydrates in a multitude of biological processes, there has been a sustained interest in developing effective glycosylation methods to enable more thorough investigation of their essential functions. Among the myriad technologies available for stereoselective glycoside bond formation, dehydrative glycosylation possesses a distinct advantage given the unique properties of C1‐alcohols such as straightforward preparation, stability, and a general reactivity compatible with a diverse set of reaction conditions. In this Focus Review, a survey of direct dehydrative glycosylations of C1‐alcohols is provided with an emphasis on recent achievements, pervading limitations, mechanistic insights, and applications in total synthesis. Abstract : Can you C1, too? A direct conversion of C1 hemiacetals into glycosides is one of the most direct method for chemical glycosylation. In this Focus Review, a survey of dehydrative strategies is provided with emphasis on recent developments and future directions.